Being an obstetrics and gynaecology resident during the COVID-19: Impact of the pandemic on the residency training program. (October 2020) - Bitonti, Giovanna; Palumbo, Anna Rita; Gallo, Cinzia; Rania, Erika; Saccone, Gabriele; De Vivo, Valentino; Zullo, Fulvio; Di Carlo, Costantino; Venturella, Roberta
Abstract: Objective: to evaluate the impact of the COVID-19 pandemic on the obstetrics and gynecology residency training program in Italy. Study design: This was a cross-sectional survey study aimed to assess the impact of the COVID-19 pandemic on the obstetrics and gynecology residency training program in Italy. An online survey with 45 questions was sent and completed anonymously by residents after accepting an informed consent. The invitation to the online survey was sent to all the Italian residents in obstetrics and gynecology. Those on maternity leave at the time of the study were excluded. Residents were asked about their routinely activity before the COVID-19 pandemic, and to report the reduction in their clinical practice. They were also asked about psychological impact of COVID-19 on their clinical practice. Results: 933 Italian residents in obstetrics and gynecology, were invited for this survey study. Four-hundred and seventy-six (51 %) completed the survey and were included in the study. Three-hundred and eighty-seven (81.3 %) were female, and 89 (18.7 %) were male. Residents age ranged from 25 to 42. In 71, 8 % (342/476) of the cases residents work in a COVID-19 reference Hospitals. One-hundred and eighty-four out of 76 residents (38.6 %) were tested on RT-PCR assay of nasal and pharyngeal swab specimens, and of them 12/184 (6.5 %) were positive to SARS−COV-2. Regarding the use of personal protective equipment (PPE), 267 (56.1 %) reported to receive adequate device, and 379 (79.6 %) felt to be well informed about prevention and management protocols. Three-hundred and thirty-one residents (69.5 %) reported to have managed COVID-19 positive patients. For 54, 7 % of respondent residents, training activity in general decreased significantly during the COVID-19 epidemic. A one-third reduction was reported in 31, 4 % of the cases, whereas a total suspension of the training in 9, 9 % of the cases. In 89, 3 % of cases the reduction was caused by the reorganization of work. Anxiety about the professional future was reported in 84 % of the residents, and 59 % of them had the perception that their training was irreversibly compromised. Conclusions: Among Italian residents in obstetrics and gynecology, COVID-19 pandemic was associated with a significant training impairment.